Pengaruh Proses Rekrutmen dan Seleksi Terhadap Kinerja Karyawan - Novatama Bagus Kuntjoro; Rusdi Hidayat Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Recruitment and selection system within PT Panca Putera Cipta Perkasa. not only producing employees whose status is permanent employees, but to increase the company's effectiveness, PT Panca Putera Cipta Perkasa. also uses labor that comes from outsourcing. The purpose of this research is to determine the effect of the recruitment and selection process on employee performance at PT Panca Putera Cipta Perkasa. This research is quantitative research, the population in this research is employees of PT Panca Putera Cipta Perkasa who are still actively working, totaling 52 employees. The sample in this study was 52 people. Data collection methods through observation, interviews and documentation. Data analysis methods use multicollinearity test, normality test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, coefficient of determination (R2), and hypothesis testing. The research results show that together (simultaneously) the recruitment and selection process has a significant effect on employee performance. Separately (partially) the recruitment process does not have a significant effect on employee performance. Meanwhile, the selection variable has a significant effect on employee performance.